ExoCarta: A Web-Based Compendium of Exosomal Cargo. Issue 4 (22nd February 2016) - Keerthikumar, Shivakumar; Chisanga, David; Ariyaratne, Dinuka; Al Saffar, Haidar; Anand, Sushma; Zhao, Kening; Samuel, Monisha; Pathan, Mohashin; Jois, Markandeya; Chilamkurti, Naveen; Gangoda, Lahiru; Mathivanan, Suresh
Abstract: Exosomes are membranous vesicles that are released by a variety of cells into the extracellular microenvironment and are implicated in intercellular communication. As exosomes contain RNA, proteins and lipids, there is a significant interest in characterizing the molecular cargo of exosomes. Here, we describe ExoCarta (http://www.exocarta.org ), a manually curated Web-based compendium of exosomal proteins, RNAs and lipids. Since its inception, the database has been highly accessed (> 54, 000 visitors from 135 countries). The current version of ExoCarta hosts 41, 860 proteins, > 7540 RNA and 1116 lipid molecules from more than 286 exosomal studies annotated with International Society for Extracellular Vesicles minimal experimental requirements for definition of extracellular vesicles. Besides, ExoCarta features dynamic protein–protein interaction networks and biological pathways of exosomal proteins. Users can download most often identified exosomal proteins based on the number of studies. The downloaded files can further be imported directly into FunRich (http://www.funrich.org ) tool for additional functional enrichment and interaction network analysis. Graphical Abstract: Highlights: ExoCarta is a Web-based compendium of exosomal proteins, RNAs and lipids. ExoCarta database is manually curated by expert biologist and also allows community annotation. ExoCarta host protein–protein interaction networks and biological pathways of exosomal proteins. Nearly 25% of the human proteins are known to be secreted via exosomes.